(3GdEjVGM aj TQM eaJGM GdYdhes
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf agPG cJGH ai Yde GdHdGZI hJhGHYgG JQLeJg HGdGjVGM hLYdJg Ydi JQJjH eNJUQ GdPi SejJg JdNjU GdeaJGM s
(3BNQgG (B:s
(3hLejY ahGJM GdShQ hNhGJjegG Ydi CMSf hLhg GdHdGZI hGcedgG eXgQ Pdc HGdHGA eOajgG eY GdJPcQ deG JbOe ef GdCUhd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B159 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B728s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs